Peggy the always sorry pigeon - Meddour, Wendy (Little Bee Books, 2024)
"Peggy is an apologetic pigeon. She automatically says she's sorry for everything, even when she hasn't done anything wrong, or when she's the one getting picked on. But Joan a seagull who sees the trouble this is causing for Peggy, gives her a nudge to stand up for herself. This tale from award-winning author Wendy Meddour contains an important message about the importance of being assertive"--